Health Effects and Public Health Concerns of Energy Drink Consumption in the United States: A Mini-Review - Al-Shaar, Laila; Vercammen, Kelsey; Lu, Chang; Richardson, Scott; Tamez, Martha; Mattei, Josiemer (Frontiers in Public Health, 2017)
As energy drink consumption continues to grow worldwide and within the United States, it is important to critically examine the nutritional content and effects on population health of these beverages. This mini-review summarizes the current scientific evidence on health consequences from energy drink consumption, presents relevant public health challenges, and proposes recommendations to mitigate these issues. Emerging evidence has linked energy drink consumption with a number of negative health consequences such as risk-seeking behaviors, poor mental health, adverse cardiovascular effects and metabolic, renal, or dental conditions. Despite the consistency in evidence, most studies are of cross-sectional design or focus almost exclusively on the effect of caffeine and sugar, failing to address potentially harmful effects of other ingredients. The negative health effects associated with energy drinks are compounded by a lack of regulatory oversight and aggressive marketing by the industry towards adolescents. Moreover, the rising trend of mixing energy drinks with alcohol presents a new challenge which researchers and public health practitioners must address further. In order to curb this growing public health issue, policy makers should consider creating a separate regulatory category for energy drinks, setting an evidence-based upper limit on caffeine, restricting sales of energy drinks, and regulating existing ED marketing strategies, especially among children and adolescents.